Drugs to block cytokine signaling for the prevention and treatment of inflammation induced preterm birth - Ng, Pearl Y.; Ireland, Demelza J.; Keelan, Jeffrey A. (Frontiers in Immunology, 2015)
Preterm birth (PTB) at less than 37 weeks of gestation is the leading cause of neonatal morbidity and mortality. Intrauterine infection (IUI) due to microbial invasion of the amniotic cavity is the leading cause of early PTB (<32 weeks). Commensal genital tract Ureaplasma and Mycoplasma species, as well as Gram-positive and Gram-negative bacteria, have been associated with IUI-induced PTB. Bacterial activation of Toll-like receptors and other pattern recognition receptors initiates a cascade of inflammatory signaling via the NF-κB and p38 mitogen-activated protein kinase (MAPK) signaling pathways, prematurely activating parturition. Antenatal antibiotic treatment has had limited success in preventing PTB or fetal inflammation. Administration of anti-inflammatory drugs with antibiotics could be a viable therapeutic option to prevent PTB and fetal complications in women at risk of IUI and inflammation. In this mini-review, we will discuss the potential for anti-inflammatory drugs in obstetric care, focusing on the class of drugs termed “cytokine suppressive anti-inflammatory drugs” or CSAIDs. These inhibitors work by specifically targeting the NF-κB and p38 MAPK inflammatory signaling pathways. Several CSAIDs are discussed, together with clinical and toxicological considerations associated with the administration of anti-inflammatory agents in pregnancy.